2023
DOI: 10.1186/s13321-022-00660-1
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionally reduced machine learning model for predicting single component octanol–water partition coefficients

Abstract: MF-LOGP, a new method for determining a single component octanol–water partition coefficients ($$LogP$$ LogP ) is presented which uses molecular formula as the only input. Octanol–water partition coefficients are useful in many applications, ranging from environmental fate and drug delivery. Currently, partition coefficients are either experimentally measured or predicted as a function of structural fragments, topological descriptors, or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Regarding the RMSD found, there is a lack of consensus about under what deviation may be admissible. For instance, Kenney et al 24 reported RMSD = 1 as a good value for octanol−water partition coefficient predictions. Instead, Vilas-Boas et al claimed that acceptable RMSD values should be lower than 0.5.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Regarding the RMSD found, there is a lack of consensus about under what deviation may be admissible. For instance, Kenney et al 24 reported RMSD = 1 as a good value for octanol−water partition coefficient predictions. Instead, Vilas-Boas et al claimed that acceptable RMSD values should be lower than 0.5.…”
Section: ■ Resultsmentioning
confidence: 99%
“…73 On the other hand, more complex ML methods such as RFR have been used to describe the quantitative structure-property relationships with lipophilicity. 74,75 Following these studies, MLR and RFR are used here for predicting the log P tol/w values of 252 neutral compounds that encompass a diverse range of physicochemical properties (Fig. 3).…”
Section: Prediction Of Log P Tol/w By Mlr and Rfr Modelsmentioning
confidence: 99%
“…hydrophobic area and chain descriptors [73], and QM-based electronic properties [74]. On the other hand, more complex ML methods such as RFR have been used to describe the quantitative structure-property relationships with lipophilicity [75,76]. Following these studies, MLR and RFR are used here for predicting the logPtol/w values of 252 neutral compounds that encompass a diverse range of physicochemical properties (Fig.…”
Section: Prediction Of Logptol/w By Mlr and Rfr Modelsmentioning
confidence: 99%